Application of 3D printed patient-specific instruments in the treatment of large tibial bone defects by the Ilizarov technique of distraction osteogenesis - Zheng, Hao; Wang, Lili; Jiang, Wenbo; Qin, Ruiqing; Zhang, Zhiyu; Jia, Zhuqing; Zhang, Jian; Liu, Yong; Gao, Xuejian (Frontiers in Surgery, 2023)
Background The Ilizarov technique of distraction osteogenesis is an effective treatment for tibia defect. However, repeated attempts to reduce due to the complexity of the bone defect during the operation will increase the operation time and iatrogenic injury, and excessive radiation exposure. Three-dimensional (3D)-printed patient specific instrument (PSI) for preoperative 3D planning and intraoperative navigation have the advantages of accuracy and visualization. The purpose of this study is to investigate whether 3D-printed PSI is helpful to correct tibial bone defects accurately and effectively. Method From May 2019 to September 2022, 19 patients with tibial bone defects were treated, including 9 males and 10 females, aged 37-64 years. All were treated with Ilizarov technique of distraction osteogenesis. 3D-printed PSI was used in 9 cases, while traditional surgery was used in 10 cases. During the operation, PSI was used to assist in reduction of tibia. Operation times were recorded in all cases, the number of fluoroscopy during the operation, and the varus/valgus, anteversion/reversion angle after the operation were measured. All measurement data were expressed by means ±SD, and Student’s t test was used to examine differences between groups. The chi square test or Fisher's precise test was used to compare the counting data. Result All PSI matched well with the corresponding tibia bone defect, and were consistent with the preoperative plan and intraoperative operation. The affected limb had a good reduction effect. The operation time from the beginning of PSI installation to the completion of Ilizarov ring fixator installation was 31.33±3.20 minutes, while that in the traditional operation group was 64.10±6.14 minutes (P<0.001). The times of fluoroscopy in the PSI group during operation was 10.11±1.83, and that in the traditional operation group was 27.60±5.82. The reduction effect of tibia in PSI group was better than that in traditional operation group, with the average angle of PSI group is 1.21±0.24°, and that of traditional operation group is 2.36±0.33°(P＜0.001). Conclusion The PSI simplifies procedures, reduces the difficulty of the operation, improves the accuracy of the operation, and provides a good initial position when used in distraction osteogenesis to treat the tibial defects.